A synthesis of tree functional traits related to drought‐induced mortality in forests across climatic zones. Issue 6 (18th February 2017) - O'Brien, Michael J.; Engelbrecht, Bettina M. J.; Joswig, Julia; Pereyra, Gabriela; Schuldt, Bernhard; Jansen, Steven; Kattge, Jens; Landhäusser, Simon M.; Levick, Shaun R.; Preisler, Yakir; Väänänen, Päivi; Macinnis‐Ng, Cate
Summary: Forest dieback caused by drought‐induced tree mortality has been observed world‐wide. Forecasting which trees in which locations are vulnerable to drought‐induced mortality is important to predict the consequences of drought on forest structure, biodiversity and ecosystem function. In this paper, our central aim was to compile a synthesis of tree traits and associated abiotic variables that can be used to predict drought‐induced mortality. We reviewed the literature that specifically links drought mortality to functional traits and site conditions (i.e. edaphic variables and biotic conditions), targeting studies that show clear use of tree traits in drought analysis. We separated the review into five climatic zones to determine global vs. regionally restricted relationships between traits and mortality. Our synthesis identifies a number of traits that have clear relationships with drought‐induced mortality (e.g. wood density at the species level and tree size and growth at the individual level). However, the lack of direct relationships between most traits and drought‐induced mortality highlights areas where future research should focus to broaden our understanding. Synthesis and applications . Our synthesis highlights established relationships between traits and drought‐induced mortality, presents knowledge gaps for future research focus and suggests monitoring and research avenues for improving our understanding of drought‐induced mortality. It is intended to assist ecologists and natural resource managers choose appropriate and measurable parameters for predicting local and regional scale tree mortality risk in different climatic zones within constraints of time and funding availability. Abstract : Our synthesis highlights established relationships between traits and drought‐induced mortality, presents knowledge gaps for future research focus and suggests monitoring and research avenues for improving our understanding of drought‐induced mortality. It is intended to assist ecologists and natural resource managers choose appropriate and measurable parameters for predicting local and regional scale tree mortality risk in different climatic zones within constraints of time and funding availability.